Pharmacokinetic–pharmacodynamic analysis of cefmetazole against extended-spectrum β-lactamase-producing Enterobacteriaceae in dogs using Monte Carlo Simulation - Kusumoto, Mizuki; Motegi, Tomoki; Uno, Haruna; Yokono, Mizuki; Harada, Kazuki (Frontiers in Veterinary Science, 2023)
The spread of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) is a serious concern in companion animal medicine owing to their ability to develop multidrug resistance. Cefmetazole (CMZ) is a candidate drug for treating ESBL-E infections; however, its regimen in dogs has not been established. In this study, we investigated the pharmacokinetic (PK) indices of CMZ in dogs and performed PK-pharmacodynamic (PD) analyses using Monte Carlo Simulation (MCS). In total, six healthy dogs received an intravenous bolus dose of CMZ (40 mg/kg body weight). Serum CMZ concentrations were evaluated using liquid chromatography-mass spectrometry, and PK indices were determined based on non-compartmental analysis. The PK-PD cut-off (COPD) values were calculated as the highest minimum inhibitory concentration (MIC) that achieved ≥90% probability of target attainment for a target value of unbounded drug concentration exceeding 40% of the dosing interval. The cumulative fraction of response (CFR) was calculated based on the MIC distribution of wild-type ESBL-E from companion animals. The area under the concentration-time curve and elimination half-time were 103.36 ± 7.49 mg•h/L and 0.84 ± 0.07 h, respectively. MCS analysis revealed that COPD values for regimens of 40 mg/kg q12, q8h, and q6h were ≤0.5, ≤2, and ≤4 µg/mL, respectively. A regimen of 40 mg/kg q6h was estimated to achieve a CFR of 80-90% for Escherichia coli and Klebsiella pneumoniae. By contrast, all regimens exhibited a CFR of ≤70% for Proteus mirabilis and Enterobacter cloacae. Therefore, we conclude that CMZ at 40 mg/kg q6h could be a viable treatment regimen for dogs infected with ESBL-producing Escherichia coli and Klebsiella pneumoniae.